Operationalising resilience in tropical agricultural value chains - Aboah, Joshua; Wilson, Mark M.J.; Rich, Karl M.; Lyne, Michael C. (Emerald Publishing Limited, 2019)
The analysis of the concept of resilience in supply chain management studies mostly focuses on the downstream side of the value chain and tacitly assumes an unlimited supply of raw materials. This assumption is unreasonable for agricultural value chains, as upstream disruptions clearly have a material impact on the availability of raw materials, and indeed, are a common source of supply problems. This paper aims to present a framework for the operationalisation of the concept of socioecological resilience in agricultural value chains that incorporates upstream activities.A citation network analysis was adopted to review articles. A conceptual framework is then advanced to identify elements of resilience and indicators relevant to tropical agricultural value chains.There are limited studies that assess resilience in the food chain context. Flexibility, collaboration, adaptability and resourcefulness are key elements for assessing resilience at the individual chain actor level. However, the paper argues that adaptability is the relevant element for the assessment of resilience at an aggregate food system level because it considers the alteration of a system’s state of resilience.The proposed framework and propositions accommodate stakeholder interactions in the value chain and could serve as a tool to guide the assessment of resilience in agricultural value chains.This paper is one of the few to extend resilience to cover the socioecological interaction aspects for supply chains that yield the raw materials needed for continuity in channel-wide value creation processes.